The new law and economic development a critical appraisal - Trubek, David M. 1935- (Cambridge University Press, 2006)
This book is a collection of essays that identify and analyze a new phase in thinking about the role of law in economic development and in the practices of development agencies that support law reform. The authors trace the history of theory and doctrine in this field, relating it to changing ideas about development and its institutional practices. The essays describe a new phase in thinking about the relation between law and economic development and analyze how this rising consensus differs from previous efforts to use law as an instrument to achieve social and economic progress. In analyzing the current phase, these essays also identify tensions and contradictions in current practice. This work is a comprehensive treatment of this emerging paradigm, situating it within the intellectual and historical framework of the most influential development models since World War II.